Multicentre observational screening survey for the detection of CTEPH following pulmonary embolism. Issue 4 (5th April 2018) - Coquoz, Nicolas; Weilenmann, Daniel; Stolz, Daiana; Popov, Vladimir; Azzola, Andrea; Fellrath, Jean-Marc; Stricker, Hans; Pagnamenta, Alberto; Ott, Sebastian; Ulrich, Silvia; Györik, Sandor; Pasquier, Jérôme; et al.
Chronic thromboembolic pulmonary hypertension (CTEPH) is a severe complication of pulmonary embolism. Its incidence following pulmonary embolism is debated. Active screening for CTEPH in patients with acute pulmonary embolism is yet to be recommended. This prospective, multicentre, observational study (Multicentre Observational Screening Survey for the Detection of Chronic Thromboembolic Pulmonary Hypertension (CTEPH) Following Pulmonary Embolism (INPUT on PE); ISRCTN61417303) included patients with acute pulmonary embolism from 11 centres in Switzerland from March 2009 to November 2016. Screening for possible CTEPH was performed at 6, 12 and 24 months using a stepwise algorithm that included a dyspnoea phone-based survey, transthoracic echocardiography, right heart catheterisation and radiological confirmation of CTEPH. Out of 1699 patients with pulmonary embolism, 508 patients were assessed for CTEPH screening over 2 years. CTEPH incidence following pulmonary embolism was 3.7 per 1000 patient-years, with a 2-year cumulative incidence of 0.79%. The Swiss pulmonary hypertension registry consulted in December 2016 did not report additional CTEPH cases in these patients. The survey yielded 100% sensitivity and 81.6% specificity. The second step echocardiography in newly dyspnoeic patients showed a negative predictive value of 100%. CTEPH is a rare but treatable disease. A simple and sensitive way for CTEPH screening in patients with acute pulmonary embolism is recommended. Chronic thromboembolic pulmonary hypertension is an uncommon disease; active screening of CTEPH in patients after acute pulmonary embolism should be considered http://ow.ly/mmFI30j3Lca